Implementing Net Promoter Score Process in Selected Insurance Companies in Metro Manila - Duyag, Romeo S. Jr (University of the Philippines Diliman, 2013)
In this project study, insurance is defined as the equitable transfer of the risk of a loss in exchange for payment. A company that sells insurance is called insurer while the one who buys is called policy holder. The amount being charged for a certain amount of insurance coverage is called premium. Insurance policy prepares and protects individuals for unexpected future financial loss. One type of insurance is life insurance (LI). Life insurance is a contract between an insured (insurance policy holder) and an insurer or assurer, where the insurer promises to pay a designated beneficiary a sum of money (the "benefits") upon the death of the insured person. LI or life-based contracts tend to fall into two major categories. One is protection policies and the other is investment policies. The former means mostly for lump sum while the latter means commonly for growth of capital by single premium. Insurance parties' relationship includes insured and the policy owner. Insured is the participant in the contract while the policy owner is the guarantor, although, owner and insured can be the same person. On the other hand, the other type of insurance is the non-life insurance (NLI) which includes automobile and homeowners policies or any insurance that is not determined to be LI.